'Getting them on board': Musculoskeletal physiotherapists conceptions of management of persons with low back pain. (1st November 2020) - Cosgrove, Josh; Hebron, Clair
Abstract: Objective: Low back pain (LBP) is the leading cause of disability worldwide; however, the majority of LBP is non‐specific in nature with no clearly identifiable source of pain. Contemporary understanding of LBP highlights the multidimensional nature of LBP and as a result clinical practice and guidelines have evolved and advocate a multidimensional approach to managing persons with LBP. This change in understanding and practice provides challenges for physiotherapists and persons with LBP, many who have biomedical views. The aim of this study was to explore musculoskeletal physiotherapists conceptions towards the management of LBP. Method: The research employed a phenomenographic inspired approach which aims to explore variations in conceptions, beliefs and understanding of a phenomenon. Six participants (physiotherapists) were interviewed via semi‐structured interviews to explore their experiences of managing persons with LBP and the data was analysed using a phenomenographic framework. Results: Three main categories emerged from the participants descriptions: the perceived role of preferences and expectations, therapeutic alliance development and getting the person "on board". Conclusion: Participants descriptions implied a therapist centred view towards the care they provided for persons with LBP. The perceived role of expectations was a significant aspect within the participants descriptions of the management of LBP. Last, the participants described the perceived development of a therapeutic alliance. These categories suggest how the physiotherapists interviewed in this study conceive the management of LBP, and these findings will provide a greater understanding around the physiotherapy management of LBP.